NW [compact disc, unabridged] : a novel - Smith, Zadie (Penguin Group USA, 2012)
Zadie Smith's brilliant tragi-comic new novel follows four Londoners - Leah, Natalie, Felix and Nathan, as they try to make adult lives outside of Caldwell, the council estate of their childhood. From private houses to public parks, at work and at play, their London is a complicated place, as beautiful as it is brutal, where the thoroughfares hide the back alleys and taking the high road can sometimes lead you to a dead end.